Physical response to a simulated period of soccer-specific fixture congestion - Page, R. M.; Marrin, K.; Brogden, C. M.; Greig, M. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to assess the physiological, perceptual, and mechanical measures associated with the completion of a simulated period of short-term soccer-specific fixture congestion. Ten male semiprofessional soccer players completed 3 trials of a treadmill-based match simulation, with 48 hours interspersing each trial. A repeated measures general linear model identified significantly (p = 0.02) lower knee flexor peak torque (PT) recorded at 300°·s-1 in the second (141.27 ± 28.51 N·m) and third trials (139.12 ± 26.23 N·m) when compared with the first trial (154.17 ± 35.25 N·m). Similarly, muscle soreness (MS) and PT data recorded at 60°/s were significantly (p = 0.05) different in the third trial (MS = 42 ± 25 a.u; PT60 = 131.10 ± 35.38 N·m) when compared with the first trial (MS = 29 ± 29 a.u; PT60 = 145.61 ± 42.86 N·m). Significant (p = 0.003) differences were also observed for mean electromyography (EMGmean) of bicep femoris between the third trial (T0-15 = 126.36 ± 15.57 µV; T75-90 = 52.18 ± 17.19 µV) and corresponding time points in the first trial (T0-15 = 98.20 ± 23.49 µV; T75-90 = 99.97 ± 39.81 µV). Cumulative increases in perceived exertion, heart rate, oxygen consumption, blood lactate concentrations, EMGmean, and PlayerLoad (PL) were recorded across each trial. Muscle soreness and PT were also significantly different after trial. There were, however, no significant main effects or interactions for the salivary immunoglobulin A and the medial-lateral PL metrics. These data suggest a biomechanical and muscular emphasis with residual fatigue, with implications for injury risk and the development of recovery strategies.